Envelope proteins as antiviral drug target. (25th November 2020) - Verma, Jyoti; Subbarao, Naidu; Rajala, Maitreyi S.
Abstract: Attachment of a virus with a specific receptor on the cell surface is the first and foremost step in virus infection. In case of enveloped viruses, their interaction with the host cell receptor is mediated by viral encoded glycoproteins on its envelope, a host derived lipid bilayer. Since, virus entry is a multistep process, after receptor recognition, envelope proteins mediate internalisation of virus particles into the host cell. Envelope glycoproteins are the first proteins that the host immune system encounters upon infection. Thus, envelope proteins are important drug target with multiple strategies to inhibit entry of the virus into the host. Currently, there are very few drugs that function as envelope protein inhibitors which are approved for human use. Here, we reviewed different classes of envelope proteins of various viruses and emphasised the use of small molecules to inhibit fusion of envelope proteins. Based on the available information in the literature, envelope proteins can be important drug targets and small molecules inhibitors can serve as potential antiviral drugs to block viral infection at an initial stage.